2021
DOI: 10.1186/s12974-021-02261-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the interrelationship between TNF-α and oxidative stress status in first-episode drug-naïve schizophrenia

Abstract: Background Increasing evidence indicates that dysregulated TNF-α and oxidative stress (OxS) contribute to the pathophysiology of schizophrenia. Additionally, previous evidence has demonstrated sex differences in many aspects of schizophrenia including clinical characteristics, cytokines, and OxS markers. However, to the best of our knowledge, there is no study investigating sex differences in the association between TNF-α, the OxS system, and their interaction with clinical symptoms in schizoph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…Thus, we did not include food preference or exercise status in our logistic regression analyses. Gender differences are also important influencing factors in clinical research [ 55 , 56 ]. In examining gender differences in the occurrence of MetS with clozapine, Zhang et al have found that MetS prevalence in schizophrenic patients treated with CLZ differed significantly as a function of gender [ i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we did not include food preference or exercise status in our logistic regression analyses. Gender differences are also important influencing factors in clinical research [ 55 , 56 ]. In examining gender differences in the occurrence of MetS with clozapine, Zhang et al have found that MetS prevalence in schizophrenic patients treated with CLZ differed significantly as a function of gender [ i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Salem et al [ 30 ] surveyed on the nurses’ population found a significant positive correlation between MDA levels and ERI model occupational stress. Previous studies found that due to the secretion of testosterone, aging, and other factors, males and young people have significantly lower MDA levels than females and old people, respectively [ 44 , 45 ]. The difference between our study and Salem’s study may be because the subjects of our study were employees of a power grid enterprise, and a relatively large proportion of the study population was 40–50.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not assess this effect in our meta-analysis, as BMI was missing in 54% of the included studies. Sex differences in MDA concentrations have been demonstrated in healthy adults [71]. For instance, urinary MDA concentrations were reported to be higher in healthy young men compared to age-matched women [72].…”
Section: Heterogeneity In Data Collection Of Demographicsmentioning
confidence: 99%